2017
DOI: 10.19082/5531
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus and its relation with obesity in Turaif (Saudi Arabia) in 2017

Abstract: BackgroundThe significant increase in the prevalence of obesity over past decades caused the concomitant rise in the incidence of glucose intolerance and diabetes.ObjectiveTo determine the prevalence of diabetes among Saudi nationals in Turaif, Kingdom of Saudi Arabia and to examine the association between diabetes and obesity in the studied population.MethodsThis study was conducted during the period from May 01 to May 31, 2017. Data was collected from 402 individuals aged between 6–63 years via a predesigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…These findings are in concordance with several studies which reported a significant effect of age on the occurrence of diabetes. [ 21 22 ] However, other studies reported an inverse linear relationship between BMI and age groups. [ 11 23 ] Difference in study settings and population may account for the difference in results.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in concordance with several studies which reported a significant effect of age on the occurrence of diabetes. [ 21 22 ] However, other studies reported an inverse linear relationship between BMI and age groups. [ 11 23 ] Difference in study settings and population may account for the difference in results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Saudi Arabia, a study revealed data similar to our study, showing that among diabetic patients, the prevalence of BMI of ≥25 was 85.7% compared to nondiabetics (72.5%) (p < 0.001). A higher prevalence of obesity (BMI ≥25) was seen in females (87.7%) than males (83.1%) [16]. Moreover, a systematic literature review of studies of obesity and hypertension prevalence in people with diabetes in different parts of the world showed that among 44 studies, obesity prevalence rates by BMI were well above 30% in 38 of 44 of the studies.…”
Section: Discussionmentioning
confidence: 97%
“…Based on available evidence, the prevalence of T2DM has linearly increased from 18.2% in 2005 to 31.6% in 2011 (3,4), and the country-based prevalence is on the rise. As with other countries, diabetes in Saudi Arabia is linked to the growing burden of obesity (5).…”
Section: Introductionmentioning
confidence: 99%